Comparative study of resistance to heat in two species of leaf-cutting ants - Bouchebti, S.; Jost, C.; Caldato, N. [UNESP]; Forti, L. C. [UNESP]; Fourcassie, V. (Springer, 2015)
Atta laevigata and Atta capiguara are two species of leaf-cutting ants that are found in the pastures of Central Brazil and build huge underground nests linked to the outdoor environment by underground tunnels, which can reach several tens of meters and further extend through foraging trails to distant foraging grounds. The tunnels built by mature colonies of A. capiguara are usually longer and deeper than those built by mature colonies of A. laevigata. The physical trails are also shorter on average. We hypothesized that these differences could be related to differences in thermotolerance between the two species. To test this we collected ants on foraging trails and placed them individually in waterproof test tubes plunged in a thermostatic bath at 25 A degrees C (control), 37 and 39 A degrees C (test temperatures). The results showed that at both 37 and 39 A degrees C, the survival time of A. laevigata was much more extended than that of A. capiguara. A possible explanation for the longer and deeper underground foraging tunnels, as well as the shorter foraging trails, built by A. capiguara may thus be their lower resistance to heat stress. The longer tunnels built by A. capiguara colonies may reduce the exposure to heat of the foraging workers that commute between their nest and the foraging grounds or act as a thermal refuge in which the workers can find temporary protection against high outdoor temperatures.
Keywords: Leaf-cutting ants; Atta laevigata; Atta capiguara; Longevity; Thermotolerance